Metamorphe Entwicklung von retrograd überprägten eklogitfaziellen Gesteinen in dem paläoproterozoischen Nagssugtoqidian Orogen in Südost-Grönland : Metamorphic evolution of relict eclogite-facies rocks in the Paleoproterozoic Nagssugtoqidian Orogen, South-East Greenland - Müller, Sascha (RWTH Aachen University, 2018)
Dissertation, Rheinisch-Westfälische Technische Hochschule Aachen, 2018; Aachen 1 Online-Ressource (XV, 203 Seiten) : Illustrationen, Diagramme, Karten (2018). = Dissertation, Rheinisch-Westfälische Technische Hochschule Aachen, 2018 : The Nagssugtoqidian Orogen in the Tasiilaq region of South-East Greenland, is a roughly southeast-northwesttrending, ~200 km wide Paleoproterozoic collisional orogen. It predominantly consists of a variety of Archean and Paleoproterozoic rocks, which were variably affected by several stages of deformation and metamorphism. The orogen has been subdivided into three different terranes. From north to south, these are the medium-pressure granulite-facies Schweizerland Terrane, the mainly high-pressure amphibolite-facies Kuummiut Terrane and the low-pressure amphibolite-facies Isertoq Terrane with the calc-alkaline Ammassalik Intrusive Complex. In the Kuummiut Terrane, variably retrogressed high-pressure mineral assemblages are preserved within mafic dykes, as well as boudins and boudinaged layers of mafic to ultramafic supracrustal rock in TTG gneiss. These mineralassemblages had previously not been investigated in much detail, but may provide important insight into the conditions of subduction, metamorphism and exhumation in the Paleoproterozoic, an era from which the geothermal regimes and nature of plate-tectonic processes are not well understood and high-pressure rocks are scarce. Within the framework of a larger expedition program to South-East Greenland, this thesis investigated the mineral textural evolution, PT-path and geochronology of variably retrogressed eclogite-facies rocks of the Kuummiut Terrane, via detailed petrological and mineral textural analysis, bulk-rock and mineral chemistry, conventional geothermobarometry, pseudosection modelling, and U-Pb isotopic dating. Well-equilibrated high-pressure and amphibolite-facies mineral assemblages, with only minor replacement textures, were found in garnet-pyroxenite, garnet-amphibolite and garnet-kyanite schist. Retrogressed eclogite, in contrast, is characterized by complex mineral reaction textures and the formation of two chemically and mineralogically distinct domains, leading to domainal equilibration volumes. A clinopyroxene domain is dominated by a fine-grained, worm-like to globular, diopsideplagioclase symplectite, which is often intergrown with and partially replaced by a coarser-grained hornblende-plagioclase symplectite. The fine-grained symplectite is interpreted to have grown at the expense of omphacite, which is only preserved in a Na-rich retrogressed eclogite sample. In a garnet domain, coarse-grained garnet is surrounded and variably pseudomorphed by corona-texturedplagioclase ± amphibole ± clinopyroxene ± orthopyroxene.Geothermobarometry and pseudosection modelling, in combination with the various Mineral textures, reveal evidence for four metamorphic stages along a clockwise PT-path. Ca-rich cores of large garnet grains in retrogressed eclogite are interpreted as prograde in origin and yield PTconditions of 14-19 kbar and 600-750 °C (I), followed by eclogite-facies metamorphism at 17-19 kbar and 740-810 °C (II). The retrograde PT-evolution is initially characterized by near-isothermal decompression to high-pressure granulite-facies conditions of 13.8-15.4 kbar and 760-880 °C (III), with subsequent decompression and minor cooling to high-pressure amphibolite-facies conditions of 8.8-10.9 kbar and 660-840 °C (IV). The PT-path implies that the Kuummiut Terrane probablyexperienced an initially rapid, tectonically driven exhumation. Furthermore, a large degree in consistency in the PT-data for the variably retrogressed high-pressure rocks suggests that they underwent the same metamorphic history, with the degree of retrogression and type of replacement assemblage mainly being controlled by fluid activity.LA-SF-ICP-MS U-Pb dating was carried out on zircon, monazite, titanite and rutile from retrogressed eclogite and the garnet-kyanite schist. A large range in 207Pb/206Pb dates between 2634 ± 63 and 1617 ± 91 Ma has been obtained, of which zircon yields the oldest and rutile the youngest dates. Detrital zircon in garnet-kyanite schist gives Archean to Paleoproterozoic dates and confines the maximum deposition of the precursor to the metasediment at 2107 ± 21 Ma. In retrogressed eclogite, the oldest zircon dates at 2146 ± 63 to 2092 ± 22 Ma are proposed to reflect the age of dyke emplacement into the Archean TTG gneiss. Dyke emplacement and deposition of supracrustal rocks most likely occurred near-contemporaneously during Paleoproterozoic extension and basin formation, as indicated by overlapping dates for detrital and magmatic zircon. The remaining data characterize the metamorphic evolution of the Kuummiut Terrane, about 200 m.y. after dyke emplacement. Consistent metamorphic dates between 1891 ± 10 and 1882 ± 3 Ma are obtained from the majority of the zircon, monazite and titanite analyses. The REE and U-Pb systematics in zircon indicate decoupling during retrograde metamorphism, with the REE patterns typical of zircon growth at eclogite-facies conditions, whereas the U-Pb dates and microtextures indicate recrystallization at high-pressure amphibolite-facies conditions. Based on previous studies and a similar decoupling in the magmatic zircons, the dates are interpreted to reflect mineral growth and recrystallization during high-pressure amphibolite-facies metamorphism. Regional medium-pressure amphibolite-facies metamorphism, associated with the collision of the Rae and North Atlantic cratons, is reflected by the 1872 ± 70 to 1821 ± 31 Ma monazite and titanite dates. Afterwards, the Kuummiut Terrane experienced relatively slow erosion-controlled cooling, with only minor thermal perturbations, as identified via rutile cooling ages at 1793 ± 10 Ma, 1738 ± 14 to 1720 ± 12 Ma, 1645 ± 63 Ma and 1617 ± 91 Ma. This thesis shows that a combination of different datasets from several variably retrogressed lithologies, rather than just examining eclogite-facies mineral assemblages, provides an invaluable tool for the characterization of the tectonometamorphic evolution of a Paleoproterozoic collisional orogen. : Published by Aachen